MAKNA PERNIKAHAN DALAM PERSPEKTIF GENERASI Y DAN GENERASI Z DI KOTA PALANGKA RAYA - Halimathus Sa'diah; Dhanu Pitoyo; Anisa Pebrianti (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
Marriage is a social institution that plays an important role in society. However, social developments and changes in people’s mindset have led to differences in perspectives on marriage, particularly between Generation Y and Generation Z. This study aims to identify the meaning of marriage according to Generation Y and Generation Z and to analyze the factors influencing the differences in their perspectives on marriage in Palangka Raya City. This research employed a qualitative method with a descriptive approach. The informants consisted of eight individuals from Generation Y and Generation Z, including both married and unmarried participants. Informants were selected purposively based on criteria relevant to the research objectives. Data were collected through in-depth interviews, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that Generation Y tends to interpret marriage as an important stage of life related to social responsibility, religious values, and maturity. Meanwhile, Generation Z tends to view marriage as a life choice that requires mental, emotional, and financial readiness. These differences are influenced by economic factors, family environment, social experiences, social media, and religious values. This study shows that the meaning of marriage continues to change along with social developments and the life experiences experienced by each generation.